Implementation of Reciprocal Teaching Style to Improve Learning Outcomes of Freestyle Swimming in Students Sekolah Tinggi Olahraga Dan Kesehatan (STOK) Bina Guna: Implementation of Reciprocal Teaching Style to Improve Learning Outcomes of Freestyle Swimming in Students Sekolah Tinggi Olahraga Dan Kesehatan (STOK) Bina Guna - Muhammad Syaleh (Journal of Midwifery and Nursing, 2020)
This study aims to improve the learning outcomes of freestyle swimming in the Theory and Practice Swimming Course I by using the application of reciprocal teaching styles to students of the Physical and Recreational Education Study Program of Sports and Health (STOK) Bina Guna by 30 students. This research uses the Action Research method. The subjects in this study were students of the Health and Recreation Education Study Program at the Bina Guna College of Sport and Health (STOK) class B 2018/2019. This research was conducted with seven meetings consisting of two cycles, the first cycle that was realized through actions according to the plan and learning methods, the results were the average value of students in freestyle learning in the initial test 60 or 36.67% of students who completed, and 63.34% of students incomplete. In the first cycle, the average student results were 70 or 60% of students completed, and 40% of students did not complete. In the second cycle, which was realized through the results of the reflection of the first cycle, the results were an average of 80 or 90% of students completed and 10% of students who did not complete. Based on the results of the study it can be concluded that: (1) with the application of reciprocal teaching styles the learning outcomes of freestyle swimming increased, (2) with the application of reciprocal teaching styles applied through life aids in improving freestyle swimming learning outcomes.